1982
DOI: 10.1507/endocrj1954.29.659
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of thyroxine-induced metamorphosis by amphenone B in toad tadpoles.

Abstract: The effect of Amphenone B, an inhibitor of corticoid synthesis, on thyroxine (T4)-induced metamorphosis was studied in toad tadpoles kept in thiourea.Amphenone injections retarded T4-induced tail resorption markedly. The effect of Amphenone was nullified by aldosterone and corticosterone added to the water in which tadpoles were kept. Steroidogenic cells of adrenals in Amphenone-injected animals were enlarged markedly as compared with those in the saline-injected tadpoles or the Amphenone-injected tadpoles whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 10 publications
(5 reference statements)
1
6
0
Order By: Relevance
“…A number of thyroid hormone-driven events during climax of metamorphosis are accelerated by glucocorticoids (see reviews in Kikuyama et al, 1993;and Kaltenbach, 1996 it may not be surprising that inhibition of glucocorticoid receptor binding by RU486 has the general effect of delaying metamorphic progression. Our results are consistent with the previous observation of Kikuyama and co-workers that treatment of metamorphosing tadpoles with an agent that inhibits corticosteroid synthesis (Amphenone B) delays resorption of the tail (Kikuyama et al, 1982). The increase in wet weight following RU486 treatment is thought to be due to increased water retention.…”
Section: Discussionsupporting
confidence: 93%
“…A number of thyroid hormone-driven events during climax of metamorphosis are accelerated by glucocorticoids (see reviews in Kikuyama et al, 1993;and Kaltenbach, 1996 it may not be surprising that inhibition of glucocorticoid receptor binding by RU486 has the general effect of delaying metamorphic progression. Our results are consistent with the previous observation of Kikuyama and co-workers that treatment of metamorphosing tadpoles with an agent that inhibits corticosteroid synthesis (Amphenone B) delays resorption of the tail (Kikuyama et al, 1982). The increase in wet weight following RU486 treatment is thought to be due to increased water retention.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were obtained by others with tadpoles of different anuran species including X. laevis (Gray and Janssens, 1990; reviewed by Denver, 2009a; Kikuyama et al, 1993). A physiological role for CS in tadpole metamorphosis is supported by the findings of Kikuyama et al (1982) who showed that treatment of tadpoles with the CS synthesis inhibitor amphenone B retarded T 4 -induced tail resorption, and that this could be reversed by treatment with CS. Several investigators reported synergistic actions between CS and TH in tadpole tail explants (Kikuyama et al, 1993; Kikuyama et al, 1983).…”
Section: Discussionmentioning
confidence: 81%
“…However, treatment with a graded series of TH from low to high over successive days to mimic the developmental profile of endogenous plasma TH enables complete metamorphosis including tail resorption, and TH alone induces nearly complete tail shrinkage in culture devoid of other hormones (37, 53, 82). Even though GCs have no known action to induce tail regression, GCs synergize with TH in vitro to accelerate tail shrinkage (14, 83) and inhibition of GC signaling with amphenone B (a corticoid synthesis inhibitor) inhibited TH-induced tail resorption in vivo (84). In contrast, cortisol partly inhibited TH-induced reduction in DNA synthesis in tail epidermal cells (85), which is consistent with the observation that GCs by themselves increase tail growth in vitro (14, 83).…”
Section: Analysis Of the Sufficiency Of Th/tr Signaling In Frog Metammentioning
confidence: 99%